Pemeriksaan Kadar Kolesterol Total dan Penyuluhan Cara Menurunkan Kadar Kolesterol Total pada Lansia di Perum Puri Astapada Indah RW X, Dusun Tambak Beras, Desa Tambakrejo, Kecamatan Jombang - Sri Sayekti; Anthofani Farhan; Awaluddin Susanto (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This community service program aimed to determine the profile of total cholesterol levels among older adults and to improve their knowledge regarding strategies to reduce cholesterol levels through health education. The methods included measuring total cholesterol levels using a rapid test based on the Point-of-Care Testing (POCT) method and providing direct health education supported by educational media. The target participants were older adults aged 60 years and above residing in Puri Astapada Indah Housing Complex RW 10, Tambak Beras Hamlet, Tambakrejo Village, Jombang District. The results of total cholesterol examination showed variations in cholesterol levels among the 40 participants. Half of the respondents (20 individuals; 50%) had normal cholesterol levels (<200 mg/dL), while 10 respondents (25%) were classified as borderline high (200–239 mg/dL), and another 10 respondents (25%) had high cholesterol levels (?240 mg/dL). Older adults with high cholesterol levels generally had risk factors such as unhealthy dietary habits and insufficient physical activity. The pre-education knowledge questionnaire revealed that the majority of respondents (30 individuals; 75%) had poor knowledge, while 10 respondents (25%) had moderate knowledge. Following the health education intervention, participants' knowledge improved significantly, with all 40 respondents (100%) demonstrating good knowledge. This community service activity had a positive impact on improving older adults' understanding of cholesterol management and is expected to encourage behavioral changes toward a healthier lifestyle. Furthermore, the program served as an early detection effort to identify the risk of cardiovascular disease within the community.